Calle Velarde - Del Molino, Sergio (Sens public)

(untitled) (Département des littératures de langue française, 2009)
Calle Velarde is a short fiction inspired on the tragic figure of Michi Panero (who is named as Archi Escario), the youngest son of a Spanish poets saga who spent his last years sick and lonely in the middle of Madrid. The story told the relationship between Escario and a young woman who is obsessed with the bohemian life-style. She is looking for the last bohemian till she found Richi. Calle Velarde would be a reflection about success and loose in modern times and about the fascination for the outsiders which used to be typical in middle-class intellectuals.